Structure and physical properties of the LaBiFe2O6 Perovskite produced by the Modified Pechini Method (2017)
ABSTRACT: In this paper the synthesis of the LaBiFe2O6 material by the modified Pechini method is reported. Structural, morphologic, magnetic and optic experimental studies were performed. Rietveld refinement of x-ray diffraction patterns revealed that LaBiFe2O6 crystallizes in an orthorhombic perovskite structure (space group Pnma, # 62). Scanning electron microscopy images showed the nanometric feature of grains. X-ray dispersive spectroscopy permitted to infer the obtaining of the LaBiFe2O6 expected stoichiometry. Results of magnetic susceptibility as a function of temperature and field magnetization evidenced mixed ferromagnetism and superparamagnetism behavior at T=300 K. Mössbauer spectroscopy supported the superparamagnetic and ferromagnetic responses as a result of the nanogranular morphology and anisotropy effects. Spectrum of diffuse reflectance suggest that this material behaves as a semiconductor with energy gap Eg=2.13 eV.